(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Callosotomy, a surgical intervention aimed at severing the corpus callosum to control refractory epilepsy and other neurological conditions, is performed across diverse age groups. This study investigates the incidence, nature, and outcomes of postoperative complications in pediatric, adult, and elderly patients undergoing callosotomy. Through retrospective analysis of 25 cases from Specialized Scientific-Practical Center for Neurosurgery and Neurorehabilitation at Samarkand State Medical University and Samarkand State Medical University Multidiscipilinary Clinic, stratified by age, we highlight age-related variations in complication profiles, providing critical insights to optimize patient selection and perioperative management.